The Kurdish Issue under the Republican Era (1968-1979) AD - Banadi, Mohammed (Humanities Journal of University of Zakho, 2021)
By the end of the first global war and after the Ottoman State of Iraq was ruled by the British Mandate، the Iraqis did not accept the new reality. As the state of Iraq was formed in 1921 during which Faisal bin Sharif Al Hussein was crowned as a king and this after he annexed Southern Kurdistan under its sovereignty; thus، it became one of the components of the new state through British settlements where Great Britain focused to serve its colonial interests، to ensure its transportation routes، oil flow، and wealth. This was occurred after the absence of the Kurdish faction that is entirely distinctive from the rest of the components of modern Iraq; whether in terms of its identity، language، customs، and traditions. Therefore، the Kurds emphasized to keep the distinction of their identity by going through stages of the struggle with the central authority in Baghdad. That authority denied their identity and their historical affiliation to their geography، and even imposed the Arab identity on them; this is what they did not like whatever its form and justification is. Their situation has passed through many stages from the beginning of the period of republican rule in 1958 until 1979، as it is witnessed in many efforts to contain it، especially after the issuance of the statement of March 11th، 1970، the application of autonomy on March 11th، 1974، and ended by of Algiers Agreement of March 6th، 1975 that had serious repercussions on the course and the future of the Kurdish issue.We will attempt to discuss the evolution of this issue from 1968 to 1979 shedding light on the most important milestones and the nature of Baghdad attitudes towards it.